Manajemen Strategis Dalam Meningkatkan Mutu Pengajaran Bahasa Arab (Studi Kasus Pada MTsN 3 Ponorogo) - Utami Nur Ajizah, Ratna (Institut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2021)
This study aims to: Knowing how strategic management in improving the quality of learning Arabic at MTs Negeri 3 Ponorogo. This research is a case study research that is qualitative in nature, using the methods of observation, interviews and documentation of Madrasahs. The data analysis technique uses the theory of Miles and Huberman with the stages of data reduction, data presentation and conclusions. The results showed that strategic management in improving the quality of Arabic learning carried out by MTs Negeri 3 Ponorogo involved all stakeholders, namely by outlining and implementing all the strategies that had been formulated in the form of programmed and measurable activities. Evaluation of strategies used by MTs Negeri 3 Ponorogo through formal and informal meetings.